Metabolic insight into bacterial community assembly across ecosystem boundaries. Issue 4 (9th March 2020) - Wisnoski, Nathan I.; Muscarella, Mario E.; Larsen, Megan L.; Peralta, Ariane L.; Lennon, Jay T.
Abstract: The movement of organisms across habitat boundaries has important consequences for populations, communities, and ecosystems. However, because most species are not well adapted to all habitat types, dispersal into suboptimal habitats could induce physiological changes associated with persistence strategies that influence community assembly. For example, high rates of cross‐boundary dispersal are thought to maintain sink populations of terrestrial bacteria in aquatic habitats, but these bacteria may also persist by lowering their metabolic activity, introducing metabolic heterogeneity that buffers the population against species sorting. To differentiate between these assembly processes, we analyzed bacterial composition along a hydrological flow path from terrestrial soils through an aquatic reservoir by sequencing the active and total (active + inactive) portions of the community. When metabolic heterogeneity was ignored, our data were consistent with views that cross‐boundary dispersal is important for structuring aquatic bacterial communities. In contrast, we found evidence for strong species sorting in the active portion of the aquatic community, suggesting that dispersal may have a weaker effect than persistence strategies on aquatic community assembly. By accounting for metabolic heterogeneity in complex communities, our findings clarify the roles of local‐ and regional‐scale assembly processes in terrestrial‐aquatic meta‐ecosystems.